Upaya Meningkatkan Hasil Belajar Tematik Materi Daur Hidup Hewan Melalui Model Snowball Throwing - Siti Mas'udah (Balai Diklat Keagamaan Semarang, 2020)
Teachers should act creatively to help students understand the subject matter. The Snwoball Throwig model is a fun learning model for students because it contains elements of play. The author uses this model in class IVC MIN 1 Rembang 2019 students with the aim of improving student learning outcomes in thematic learning material life cycle material for class IVC MIN 1 Rembang in 2019, the author uses the classroom action research method with two cycles to obtain data about the abilities of students . The data obtained showed that this model significantly succeeded in improving the students' abilities in thematic learning of animal life cycle materials. The Snwoball Throwing model can be a model that can help improve students' abilities in animal life cycle material